If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -54 + -21y = 70 Solving -54 + -21y = 70 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + -21y = 70 + 54 Combine like terms: -54 + 54 = 0 0 + -21y = 70 + 54 -21y = 70 + 54 Combine like terms: 70 + 54 = 124 -21y = 124 Divide each side by '-21'. y = -5.904761905 Simplifying y = -5.904761905
| 3x-7(7-x)=8 | | 5a-6+2a=12 | | 34=4x | | -13x-19=-6s | | 2(x+a)=4bsolvea | | 14-(36-3c)=4c-c | | 2(2x+8)-4=2(x-6)+8 | | 5x-20=x-4+x+5 | | 20-(x+5)=5x-3 | | 4x-7=x+12 | | 4=7+x+6m | | 4z+9=1 | | 3x-8=6x-3 | | -12v^2+8v-16= | | 0.1x-0.7(10-3x)=-0.9(x-6) | | .50x=-10 | | 3x+4=3(x+44)+x | | 7x-9=2x+27 | | 2ab-2ac=x | | 3x-7x+4=-4(x+3) | | 6x+2(1x+3)=3x+5x+6 | | 5x+5(-2x-11)=-90 | | 5-5/3= | | 17=2x | | -3p^2-10p-8=0 | | 48=-6(5a-5)-4(-1-7a) | | 6r=2 | | 3*0+y=7 | | 7+3(2x-9)x=-1 | | S(4)=9(4)-4 | | 120=-3x+7(-2x-12) | | 3(2x-9)-2=3(x-8)+(1) |